Effectiveness of enrofloxacin for the treatment of experimentally-induced bovine anaplasmosis Eficácia da enrofloxacina no tratamento da anaplasmose bovina experimental - Elias Jorge Facury-Filho; Antônio Último de Carvalho; Paulo Marcos Ferreira; Marcelo Fonseca Moura; Bethania Campos Apolinário; Leandro de Paula Henrique Santos; Múcio Flávio Barbosa Ribeiro (Revista Brasileira de Parasitologia Veterinária, 2012)
Four groups of six Holstein calves were inoculated with 3.6 × 10(7) erythrocytes parasitized with Anaplasma marginale. The criteria for treatment of calves were increasing A. marginale rickettsemia and 30% reduction of baseline packed cell volume (PCV) of each animal. Group 1 (G1) received 7.5 mg.kg-1 of enrofloxacin in a single dose; Group 2 (G2) 7.5 mg.kg-1 of enrofloxacin twice every three days; Group 3 (G3) 20 mg.kg-1 of long-acting oxytetracycline in a single dose; and Group 4 (G4) a single dose of PBS. Physical examinations, blood smears and PCV were performed daily. On day treatment, G1, G2 and G3 animals had a mean rickettsemia of 17, 23 and 12%, respectively. At 2 days after treatment (DAT) G1 and G2 animals showed a significant reduction of rickettsemia (p < 0.05) compared to G3. G3 animals had high rates of rickettsemia in the first 2 DAT and a slow decrease until stabilization on 9 DAT. The mean PCV in G1 and G2 increased and stabilized after 7 and 8 DAT, respectively. PCV stabilization was achieved in G3 at 13 DAT. Both enrofloxacin and oxytetracycline were effective for the treatment of anaplasmosis, but enrofloxacin was faster reduction of rickettsemia and PCV recuperation (p < 0.05) compared to oxytetracycline Quatro grupos de seis bezerros da raça Holandesa foram inoculados com 3,6 × 10(7) eritrócitos parasitados com Anaplasma marginale. Os critérios para o tratamento dos bezerros foram aumento da rickettsemia do A. marginale e redução de 30% do valor basal de volume globular (VG) de cada animal. O Grupo 1 (G1) recebeu 7,5 mg.kg-1 de enrofloxacina em dose única; o Grupo 2 (G2), 7,5 mg.kg-1 de enrofloxacina duas vezes a cada três dias; o Grupo 3 (G3), 20 mg.kg-1 de oxitetraciclina de longa ação em dose única; e o Grupo 4 (G4) uma única dose de PBS. Exames físicos, esfregaço sanguíneo e VG foram realizadas diariamente. No dia do tratamento, os animais G1, G2 e G3 apresentaram rickettsemia média de 17, 23 e 12%, respectivamente. Nos primeiros 2 dias após o tratamento (DAT) os animais do G1 e G2 mostraram uma redução significativa de rickettsemia (p < 0,05) em relação ao G3. Animais do G3 tiveram altas taxas de rickettsemia nos 2 DAT e uma diminuição lenta até à estabilização em 9 de DAT. O VG médio no G1 e G2 aumentou e estabilizou após 7 e 8 DAT, respectivamente. A estabilização do VG do G3 foi aos 13 DAT. A enrofloxacina e a oxitetraciclina foram efetivas no tratamento da anaplasmose, mas a enrofloxacina apresentou redução da rickettsemia e recuperação do VG (p < 0,05) mais rápida em comparação com oxitetraciclina.